Nitrite-induced testicular toxicity in rats: therapeutic potential of walnut oil - Adelakun, Sunday A. (JBRA Assist Reprod, 2019)
OBJECTIVE: To determine the impact of walnut oil on nitrite-induced testicular toxicity in Sprague-Dawley (SD) rats. Available evidence suggests that walnut oil contains high levels of important unsaturated fatty acids including alpha-linolenic acid (ALA) and omega-3; nitrite is a reproductive toxicant that causes the loss of germ cells in the seminiferous tubules and generates oxidative stress in the testes, thus reducing sperm counts and affecting sperm morphology. METHODS: This study included 24 male and 24 female adult SD rats. The male rats randomly assigned to Group A (controls) were given normal saline 2 ml/kg. The rats in Groups B, C, and D were given 50mg/kg body weight (bwt) of walnut oil, 0.08 mg/kg bwt of nitrite, and 0.08 mg/kg bwt of nitrite + 50 mg/kg of walnut oil respectively for 28 days via gastric gavage. Tested parameters included: testicular histology, sperm parameters, reproductive hormones, fertility, malondialdehyde (MDA), superoxide dismutase (SOD), reduced glutathione, and catalase (CAT). RESULTS: A severe decrease in spermatogenic cell series, hypocellularity, tubular atrophy, decreased sperm quality, and increased MDA levels were observed in the rats given nitrite only when compared to controls. Rats given 50 mg/kg of walnut oil had significant growth of seminiferous epithelium compared to controls. The rats given walnut oil and nitrite had significant growth of seminiferous epithelium, improved sperm quality, and had decreased MDA levels. CONCLUSION: Walnut oil attenuated the deleterious effects of nitrite to the testes, reduced oxidative stress, and promoted spermatogenesis.